1993
DOI: 10.1111/j.1469-8137.1993.tb03867.x
|View full text |Cite
|
Sign up to set email alerts
|

Xylem development in relation to water uptake by roots of grapevine (Vitis vinifera L.)

Abstract: S U M M A R YAxial resistittice (/?") was e.stirtiated from xylem diameter tnieasuretnents obtaitied from periodic acid atid toluiditie blue O (PAS-TBO) staitied sectiotis of Vitis vinifera L. cv. Shiraz. Multiple litiear regressioti showed a strotig negative felationship between axial resistance atid either root diameter or distatice frotn the root tip. Water stress treatmetits did not affect the relationships, but plant age significatitly influenced the ititercept of the legrcssion. The use of both lignin at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…Engelbrecht et al (2005) suggested that decreased WUE in water-stressed seedlings might be related to their root systems which are not well-established to acquire water from lower soil layers. In addition, water stress probably resulted in more lignified roots which could decline hydraulic conductivity and water uptake (Jupp and Newman 1987;Mapfumo et al 1992;North and Nobel 1992). When soil was dried, therefore, both low growth and lignification of the roots led to very low rate of water uptake resulting decrease in WUE.…”
Section: Discussionmentioning
confidence: 99%
“…Engelbrecht et al (2005) suggested that decreased WUE in water-stressed seedlings might be related to their root systems which are not well-established to acquire water from lower soil layers. In addition, water stress probably resulted in more lignified roots which could decline hydraulic conductivity and water uptake (Jupp and Newman 1987;Mapfumo et al 1992;North and Nobel 1992). When soil was dried, therefore, both low growth and lignification of the roots led to very low rate of water uptake resulting decrease in WUE.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that hydraulic conductivity of roots, shoot nodes and internodes and petioles, as well as whole-plant conductivity decline in grapevines subjected to water stress (Schultz and Matthews 1988;Salleo and Lo Gullo 1989;Winkel and Rambal 1993;Schubert 1998, 2006;Lovisolo et al 2002aLovisolo et al , 2008aLovisolo et al , 2008bSchultz 2003a;Pou et al 2008). This decline can be due to water stress-induced changes in xylem development (Mapfumo et al 1993;Mapfumo and Aspinall 1994), but most often occurs by means of drought-induced cavitation (Schultz and Matthews 1988;Salleo and Lo Gullo 1989;Schultz 2003a). Roots and leaf petioles appear to be more sensitive than shoots to drought-induced cavitation (Schultz 2003a;Lovisolo et al 2008a), although in the shoots, internodes are much more sensitive than nodes (Salleo and Lo Gullo 1989).…”
Section: Soil Water Stress and Mechanisms Of Stomatal Closurementioning
confidence: 99%
“…Both root-system length and leaf area are constrained by negative consequences of low tissue mass density and small organ diameter (Ryser, 1998). The limits of maximizing root length by reducing tissue mass density and root diameter are set by the low hydraulic capacity (Mapfumo et al, 1993), the low tensile strength (Easson et al, 1995) and the short life span (Ryser, 1996 ;Schla$ pfer & Ryser, 1996) of thin roots with a low tissue mass density. As rootsystem length is closely associated with acquisition capacity for below-ground resources (Ryser, 1998), the already mentioned constraints are likely to influence the ecological characteristics of a species.…”
Section: mentioning
confidence: 99%